THE ROLE OF DIGITAL TECHNOLOGY IN POVERTY REDUCTION: OPPORTUNITIES AND CHALLENGES TOWARDS SUSTAINABLE DEVELOPMENT - Annazali, Ahmad Haqqi; Wahyudi, Slamet Tri (Jurnal Kajian Ilmu Hukum, 2025)
Poverty alleviation in Indonesia is increasingly dependent on digital technology, but this transformation creates new challenges related to the digital divide and data vulnerability of poor groups. Digital welfare programs, such as the distribution of social assistance based on the Integrated Social Welfare Data (DTKS), put poor communities at risk of data exploitation in the era of Civil Society 5.0, thus requiring a strong institutional architecture to protect them. This study uses a normative legal research method through a legislative and conceptual approach. The results show that the existing institution, namely the Ministry of Communication and Digital Affairs, is legally an executive body (assisting the President) that is prone to conflicts of interest in implementing the PDP Law, while the main challenges in the field are infrastructure gaps and low digital literacy. Therefore, effective implementation of the PDP Law to protect the data of the poor and support the SDGs requires the establishment of a Data Protection Authority (DPA) as an independent state auxiliary organ, the formation of which is highly dependent on the political will of the President as the highest authority.